2013
DOI: 10.1093/trstmh/trt015
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphate dehydrogenase deficient variants are associated with reduced susceptibility to malaria in the Brazilian Amazon

Abstract: G6PD enzyme activity was directly related to susceptibility to malaria in the Brazilian Amazon, where P. vivax predominates. Severe G6PDd was associated with considerable higher risk of malaria-related transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 32 publications
2
43
2
Order By: Relevance
“…Only 2 of the 15 genetically identifi ed individuals were self-identifi ed as African descendants, a result that can be explained by the mixing that has occurred among local populations. Of these carriers, 60% (9/15) had experienced up to 3 previous episodes of malaria during their lifetime, whereas 33% (5/15) had never presented with a previous episode of malaria, a result similar to that obtained in previous studies (26) (33) (37) . Ten participants had a positive diagnosis of vivax malaria at the time of blood collection.…”
Section: Discussionsupporting
confidence: 86%
“…Only 2 of the 15 genetically identifi ed individuals were self-identifi ed as African descendants, a result that can be explained by the mixing that has occurred among local populations. Of these carriers, 60% (9/15) had experienced up to 3 previous episodes of malaria during their lifetime, whereas 33% (5/15) had never presented with a previous episode of malaria, a result similar to that obtained in previous studies (26) (33) (37) . Ten participants had a positive diagnosis of vivax malaria at the time of blood collection.…”
Section: Discussionsupporting
confidence: 86%
“…FY*B/FY*X and FY*A/FY*X genotypes are associated with low parasite density, which may favorably impact hemoglobin levels (69). Observational studies have shown protection against P. vivax infections conferred by a RBC enzyme (glucose-6-phosphate dehydrogenase) deficiency (70)(71)(72) and an erythrocyte membrane disorder (Southeast Asian ovalocytosis) by a mechanism that is independent of the Duffy antigen (73). On the other hand, thalassemias, which are disorders of globin synthesis, appear to increase the susceptibility to vivax malaria in carrier populations from different geographic regions (74)(75)(76)(77).…”
Section: Overview Of the Major Determinants Of Vivax Anemiamentioning
confidence: 99%
“…1 It has a prevalence of approximately 4.5% among the male population in the Amazon region. 2,3 Diabetes mellitus is a serious public health problem because of its high prevalence, severe morbidity and mortality; it is also widely distributed. Approximately 5.6% of the Brazilian population have been diagnosed with diabetes.…”
Section: Introductionmentioning
confidence: 99%